ASSEMBLAGES OF WOOD-INHABITING MACROFUNGI SPECIES IN BEECH FORESTS FROM EASTERN ROMANIA - Ciprian Constantin BÎRSAN; Constantin MARDARI; Catalin TANASE (Journal of Plant Development)
Species composition and diversity of lignicolous fungi occurring in representative Fagus sp. forests have been analyzed along an altitude gradient, in 14 locations from the eastern region of Romania, including mountain forests (Borca, Gosman, Nemtisor, Tarcau), as well as hill forests (Arsura, Bârnova, Dalhauti, Dragomirna, Gâdinti, Homita, Humosu, Magura Ocnei, Runc, Valea Fagilor). The investigations were carried out over three successive years (2020-2022) in a total of 40 study plots with a size of 1000 square meters each. Identification of the main fungal groups was realized using a hierarchical agglomerative clustering procedure, and the differential species were determined based on their indicator value, while the relationship between fungal composition and environmental variables was assessed with detrended correspondence analysis. A total of 89 species of wood-inhabiting fungi has been identified, with approximately 2500 records. These species were grouped in three different clusters: one specific to the mixed broadleaved-coniferous forest in (sub) mountain areas, one specific to hornbeam - beech communities in hilly areas, and one specific to more thermophilic forest communities with Fagus taurica. The main ecological factors influencing the fungal composition were altitude, average annual precipitations and average annual temperatures, which also influence the trees species composition of the analyzed forests.